Metodología para la generación de mapas tridimensionales a partir de fotogrametría con vehículo aéreo no tripulado - Brenes-González, Leonardo (Instituto Tecnológico de Costa Rica, 2016)
Costa Rica is a country with many natural resources, where the economic development is linked to the agricultural production. Therefore, the loss of nutrients and problems related to erosion has a high impact. Some of the causes of this phenomenon are weather conditions, poor agricultural practices, excessive fertilizer use and other factors affecting the productive potential of soils.Erosion not only affects the soil, also pollutes the water resources through sediments. One method to quantify the soil erosion is through runoff plots, which usually are bounded by walls of metal embedded in the ground and a system of receiving tanks that allow storing water and quantify sediments. In our country, runoff plots are normally used to quantify the erosion, but its disadvantages in the cost of construction, maintenance, time, training, size and difficulties measuring make it a not effective method. Therefore, an alternative to runoff plots is being explored with the technique of UAV photogrammetry for generation of three-dimensional maps as a solution to quantify erosion. This project proposes the development of a methodology for generating three-dimensional maps from UAV photogrammetric data. This methodology will quantify erosion in a more systematic, accurate, and less invasive way in comparison to the utilization of runoff plots.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Modelado; Sistemas; Mapeo digital; Fotogrametría; Erosión; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics